Neuromuscular compression garments: effects on neuromuscular strength and recovery - Bottaro, M.; Martorelli, S.; Vilaca, J. (Journal of Human Kinetics, 2011)
Graduated compression stockings have been used as a mechanical method of deep vein thrombosis prophylaxis for several years. Several studies have demonstrated an increase in mean deep venous velocity, reduced venous pooling, improved venous return, and increase blood lactate clearance in subjects who wore graduated compression stockings during exercise. A possible improvement in venous return during and after exercise may facilitate the clearance of metabolites produced during exercise. Also, studies have suggested that compressive clothing can promote tissue regeneration and consequently positively benefit the muscle function following strenuous exercise. However, the results from the previous studies are controversial. Also, the majority of the studies investigated the effects of compression stockings and there is a lack of studies using different compression garments such as compression shorts, shirts and sleeves. Thus, the purpose of this text is to briefly review the possible effects of compression garments on exercise performance and muscle recovery.